Síntoma de Ansiedad y Adicción a Redes Sociales en Adolescente de una Institución Educativa en el Distrito de Riohacha.
This study examines the relationship between anxiety symptoms and addiction to social networks in adolescents from the Livio Reginaldo Fishione Educational Institution in Riohacha, La Guajira. Using a quantitative and correlational approach, data were collected from 100 students (47% women, 53% men) between 15 and 19 years old by applying the Children and Adolescents Manifest Anxiety Scale (CMAS-R2) and the Addiction to Social Networks (ARS). The results show that 75% of the participants are free of significant anxiety, and 57% present high levels of addiction to social networks, characterized by obsession, lack of control and excessive use. However, the evaluation between anxiety and addiction was significant (0.280), suggesting that they are independent constructs